Evaluasi Program Bumilku dalam Pencegahan Angka Kematian Ibu dan Anak di Kabupaten Kulon Progo - Tarisma, Pungky Elisa Nanda; Mutmainah, Nur Fitri (Innovative: Journal Of Social Science Research, 2025)
The BumilKu program is a digital innovation in public health services developed by the Kulon Progo District Health Office to reduce maternal and infant mortality rates. This study aims to evaluate the implementation of BumilKu based on five policy evaluation indicators according to Dunn and Nurcholis, namely: effectiveness, human resources, facilities and infrastructure, socialization, and impact. The study employed a qualitative descriptive approach with data collected through interviews, observations, and document analysis. The results show that the BumilKu application is quite effective in assisting the monitoring and referral of pregnant women. However, challenges remain, particularly regarding limited human resources and lack of direct socialization to pregnant women as end-users. Although the program has not significantly reduced mortality rates, it has improved data management and provided new insights for health workers.